Use of advanced therapies for pulmonary embolism among pregnant or postpartum women. (3rd May 2023) - Farmakis, I; Barco, S; Giannakoulas, G; Keller, K; Valerio, L; Konstantinides, S V; Hobohm, L
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Pulmonary embolism (PE) in pregnancy can be a devastating event with a high case-fatality rate. Information on treatment of acute PE during pregnancy or the puerperium is limited. Purpose: To investigate the use of advanced therapies and associated outcomes in maternal-associated PE. Methods: The Nationwide Inpatients Sample (NIS) of years 2016-2018 was accessed to select hospitalizations among pregnant or postpartum women with a main discharge diagnosis code of acute PE (ICD-10 O88.2 or the combination I26 and O09). High-risk PE was defined as hospitalizations with an additional diagnosis of shock, cardiac arrest, cardiopulmonary resuscitation, or use of vasopressors. Systemic thrombolysis, catheter-directed thrombolysis, catheter-based thrombectomy, surgical embolectomy, and extracorporeal membrane oxygenation (VA-ECMO) were considered as advanced therapy. We investigated the prevalence of in-hospital fatality, abortive outcome, pre-term deliveries, caesarean sections, and bleedings. Results: During the period from 2016 to 2018, an estimated 11, 986, 555 maternal-related hospitalizations and an estimated 1, 129, 935 PE-related hospitalizations were identified. Of them, an estimated 7, 595 (0.06% of all maternal-related hospitalizations and 0.67% of all PE-related hospitalizations) were characterized as PE hospitalizations during pregnancy (48% of all) or the puerperium (52% of all), while 2.2% of them fulfilled the criteria of high-risk PE. Patients with high-risk PE showed higher prevalence of chronic arterial hypertension, heart failure, ischemic heart disease, and post-partum infections compared to not-high risk patients (Figure 1). The median length of stay in the hospital was 3 days; patients with high-risk PE had significantly greater length of stay with a median of 8 days (p<0.001). In general, in 2.6% of all pregnant or postpartum women with PE advanced therapies were used, whereas in high-risk PE patients advanced therapy was performed in 27% (p<0.001) (Figure 2). Case fatality rate was <0.1% among not-high-risk and 36% among high-risk patients (p<0.001). Case fatality rate was 0.3% among women ≤24 years, 0.9% among women 25-40 years, and 2.8% among women ≥40 years. Caesarean section (33% vs 16%, p=0.008), and bleeding (24% vs 12%, p=0.031) were more prevalent among high-risk vs not high-risk PE hospitalizations, whereas an abortive outcome was not (3% vs 1.5%, p=0.5). Conclusion(s): Case fatality in pregnant or postpartum women with high-risk PE was high, but lower than in the general population. The utilization of advanced therapies is low among pregnant or postpartum women with PE and hemodynamic instability. Figure 1 Figure 2